REKAMAN BARU BEBERAPA JENIS TUMBUHAN DI JAWA - Tutie Djarwaningsih (PTTI, 2010)
Tutie Djarwaningsih. 2010.New Record for Some Plants Species in Java. Floribunda 4(1): 15–17. — Seven species of plants collected from Mt.Tukung Gede Nature Reserved were reported as new record for Java. Those species had not been collected yet. Its were distributed in Malesian region, and deposited in “Herbarium Bogoriense” Botany Division, Research Center for Biology, Cibinong Science Center–LIPI